Addressing the Challenges of Arbitration Implementation in Indonesia - Febi Febonecci S.Brahmana; Azzahra Meutia Rahmadani; Tagor Indra Mulia Lubis; Aji Syahputra; Alfarizkie Alqorni (ISNU Sumatera Utara, 2024)
The implementation of arbitration in Indonesia faces various challenges that may affect its effectiveness as a dispute resolution method. One of the main challenges is the lack of understanding of arbitration procedures among the public and businesses, which results in uncertainty in going through the process. In addition, legal uncertainty and lack of consistent regulation may create doubts about the arbitrator's decision. Potential conflicts of interest are also an issue that needs to be addressed, especially in relation to the selection of independent and qualified arbitrators. The quality of arbitrators and arbitral institutions greatly affects the outcome of this process. Despite the existence of supportive regulations, implementation on the ground is often not optimal, thereby reducing public confidence in arbitration. To improve the effectiveness of arbitration in Indonesia, it is important to increase socialization of arbitration procedures, strengthen regulations, and ensure the independence and professionalism of arbitrators. These steps are expected to make arbitration a more reliable alternative to dispute resolution.